The association of cigarette smoking and pathological response to neoadjuvant platinum-based chemotherapy in patients undergoing treatment for urinary bladder cancer - A prospective European multicenter observational study of the EAU Young Academic Urologists (YAU) urothelial carcinoma working group. (September 2020) - Gild, Philipp; Vetterlein, Malte W.; Seiler, Roland; Necchi, Andrea; Hendricksen, Kees; Mertens, Laura S.; Roghmann, Florian; Landenberg, Nicolas V.; Gontero, Paolo; Cumberbatch, Marcus; Dobruch, Jakub; Seisen, Thomas; et al.
Abstract: Objective: To prospectively study the impact of smoking on pathological response to neoadjuvant chemotherapy (NAC) in patients undergoing radical cystectomy (RC) for urothelial carcinoma of the bladder (UCB). Materials & methods: We collected standard clinicopathological variables, including smoking status (never, former, current) in patients undergoing NAC and RC for UCB at 12 European tertiary care centers between 12/2013-12/2015. Clinicopathological variables were compared according to smoking status. Multivariable logistic regression models were built to assess the association of smoking status and a) complete (no residual disease), b) partial (residual, non-muscle invasive disease), c) no pathological response (residual muscle invasive or lymph node positive disease). Kaplan-Meier and Cox regression analyses were employed to study the impact of response to NAC on survival. Results and limitations: Our final cohort consisted of 167 NAC patients with a median follow-up of 15 months (interquartile range (IQR) 9–26 months) of whom 48 (29%), 69 (41%), and 50 (30%) where never, former, and current smokers, respectively. Smoking was significantly associated with advanced age (p = 0.013), worse ECOG performance status (p = 0.049), and decreased pathological response to NAC (p = 0.045). On multivariable logistic regression analyses, former and current smoking status was significantly associated with lower odds of complete pathological response (odds ratio (OR) 0.37, 95% confidence interval (CI) 0.16–0.87, p = 0.023, and OR 0.34, 95% CI 0.13–0.85, p = 0.021), while current smoking status was significantly associated with a greater likelihood of no pathological response (OR 2.49, 95% CI 1.02–6.06, p = 0.045). Response to NAC was confirmed as powerful predictor of survival. Conclusions: Smoking status is adversely associated with pathological response to NAC. Smokers should be informed about these adverse effects, counseled regarding smoking cessation, and possibly be considered for immunotherpeutics as they may be more effective in smokers.